Dietary nitrate intake and vegetable consumption, ambient particulate matter, and risk of hypertension in the Nurses' Health study. (March 2022) - Li, Xianggui; Zhang, Weidong; Laden, Francine; Curhan, Gary C; Rimm, Eric B; Guo, Xinbiao; Hart, Jaime E.; Wu, Shaowei
Graphical abstract: Highlights: Dietary nitrate and particulate matter have an interaction on risk of hypertension. Dietary nitrate intake is associated with a lower risk of hypertension. Ambient PM2.5 is associated with an increased risk of hypertension. Green leafy vegetables consumption is associated with a lower risk of hypertension. The benefits of dietary nitrate are attenuated by increasing exposure to ambient PM. Abstract: Background: Studies have suggested that dietary nitrate could lower blood pressure levels whereas ambient particulate matter (PM) may increase risk of hypertension. However, it is unknown if these exposures may modify each other. Objectives: We collected information on dietary nitrate intake and vegetables consumption and estimated long-term exposures to ambient PM for women in the Nurses' Health Study. Methods: Hazard ratios (HRs) and 95% confidence intervals (95% CIs) for risk of hypertension were calculated using Cox proportional hazards models with adjustment for potential demographic, lifestyle and dietary confounders. Interactions were assessed with multiplicative interaction terms and stratified models. Results: Increases in dietary nitrate intake (per 150 mg/d) and green leafy vegetables consumption (per serving/day) were both significantly associated with decreases in hypertension risk (both multivariable-adjusted HRs were 0.97, 95% CI: 0.94, 0.99). Long-term exposure to ambient PM with an aerodynamic diameter ≤ 2.5 µm (PM2.5 ) was associated with an increased risk of hypertension, with a multivariable-adjusted HR of hypertension of 1.06 (95% CI: 1.02, 1.11) per 10 µg/m 3 increase in PM2.5 . Ambient PM2.5 significantly modified the associations of dietary nitrate intake ( P interaction = 0.02) and green leafy vegetables consumption ( P interaction = 0.004). The associations with dietary factors were gradually weakened with increasing PM2.5 : the fully-adjusted HRs for risk of hypertension were 0.94 (95% CI: 0.89, 0.99) and 0.94 (95% CI: 0.90, 0.99) for per 150 mg/d increase in nitrate intake and per serving/d increase in green leafy vegetables consumption, respectively, in the lowest PM2.5 quartile, and 1.00 (95% CI: 0.94, 1.06) and 1.02 (95% CI: 0.97, 1.08), respectively, in the highest PM2.5 quartile. Conclusion: Our research highlights a potentially protective effect of dietary nitrate intake in the prevention of hypertension and suggests that these benefits are attenuated by increasing exposure to ambient PM2.5 .